2010
DOI: 10.1002/adma.200903023
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Organic Solar Cells Using a High‐Quality Crystalline Thin Film as a Donor Layer

Abstract: An efficient organic solar cell is fabricated by the weak‐epitaxy‐growth method and the achieved power conversion efficiency is over 3% (see figure). A Single‐crystal‐like thin film improves the carrier mobility and reduces the electron–hole recombination. Deposition of a zinc phthalocyanine (ZnPc):C60 mixed layer at 100 °C results in a better interpenetrating interface and the device performance is improved further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 24 publications
(29 reference statements)
2
70
0
1
Order By: Relevance
“…A number of new-generation organic solar cells are currently under investigation, including polymer/fullerene bulk heterojunction (BHJ) solar cells [5][6][7][8][9][10][11][12], and small molecule solar cells [13][14][15][16]. More recently, solution-processed solar cells using soluble organic small molecules have attracted great attention for their numerous attractive features such as high molecular purity, reproducibility and scalable synthesis, tunable optoelectronic properties through structural control and high carrier mobility [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A number of new-generation organic solar cells are currently under investigation, including polymer/fullerene bulk heterojunction (BHJ) solar cells [5][6][7][8][9][10][11][12], and small molecule solar cells [13][14][15][16]. More recently, solution-processed solar cells using soluble organic small molecules have attracted great attention for their numerous attractive features such as high molecular purity, reproducibility and scalable synthesis, tunable optoelectronic properties through structural control and high carrier mobility [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Yu mentioned that the crystalline phthalocyanine layer was formed on top of the BP2T (i.e. one of TPCOs) through "weak epitaxy growth" (WEG) [26]. In light of our experiments we assume that the WEG was caused by the aligned structure of the BP2T layer.…”
Section: Resultsmentioning
confidence: 96%
“…The point is that the TPCO underlayer produces high crystallinity of the photoelectric conversion materials [15,26]. More specifically, Yu mentioned that the crystalline phthalocyanine layer was formed on top of the BP2T (i.e.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore efficient charge extraction to improve the charge transport between the organic layer and electrode is indispensable, which can avoid the loss of energy level offset. Recent advances have shown that hole extraction layers (HELs) as a buffer layer are decisive in determining the enhanced V oc in OSCs [16][17][18][19] [19]. In this paper we present a new HEL material, TBBD for OSCs application.…”
Section: Introductionmentioning
confidence: 99%